2016
DOI: 10.1038/gt.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Reduced retinal transduction and enhanced transgene-directed immunogenicity with intravitreal delivery of rAAV following posterior vitrectomy in dogs

Abstract: Adeno-associated virus (AAV) vector-based gene therapy is a promising treatment strategy for delivery of neurotrophic transgenes to retinal ganglion cells (RGCs) in glaucoma patients. Retinal distribution of transgene expression following intravitreal injection (IVT) of AAV is variable in animal models and the vitreous humor may represent a barrier to initial vector penetration. The primary goal of our study was to investigate the effect of prior core vitrectomy with posterior hyaloid membrane peeling on patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
6
17
0
Order By: Relevance
“…24 In contrast, posterior vitrectomy and posterior hyaloid membrane peeling, in combination with transductions using capsid mutant AAV2 particles, recently were applied to a canine model but failed to increase GFP signals in the retina. 54 Boyd et al 54 observed an inflammatory response possibly against the GFP transgene and a reduced level of GFP-positive cells following vitrectomy. As our vitreous aspiration is different from vitrectomy in larger animal models and humans, it is difficult to compare these studies directly.…”
Section: Discussionmentioning
confidence: 99%
“…24 In contrast, posterior vitrectomy and posterior hyaloid membrane peeling, in combination with transductions using capsid mutant AAV2 particles, recently were applied to a canine model but failed to increase GFP signals in the retina. 54 Boyd et al 54 observed an inflammatory response possibly against the GFP transgene and a reduced level of GFP-positive cells following vitrectomy. As our vitreous aspiration is different from vitrectomy in larger animal models and humans, it is difficult to compare these studies directly.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest challenge when utilizing AAV vectors for in vivo labelling of RGCs is to overcome the inner limiting membrane, which acts as a physical barrier to achieving a high transduction rate. [54][55][56] Administering AAV vectors via intravitreal injection has been shown to be a useful method for longitudinal labelling and imaging ( Figure 5). 57 This technique provides the ability to quantify an estimate of cell density in a living animal and monitor changes in cell labelling.…”
Section: Adeno-associated Viral (Aav) Vector Labellingmentioning
confidence: 99%
“…The use of the self‐complementary AAV vectors and the recent development of novel capsid mutated AAV particles resulted in an expanded toolkit for targeting of the trabecular meshwork and other tissues within the anterior segment of the eye (Figure 3). 62,77,78,80,92‐95 The self‐complementary AAV genome facilitates the generation of double‐stranded DNA for more efficient and long‐term transduction of trabecular meshwork cells in several species, with long‐lasting effects for at least 2 years in monkeys 62,77,91 . Capsid mutant AAV2 (AAV of serotype 2) showed the highest transduction of the trabecular meshwork, followed by AAV5, AAV6, and AAV8 serotypes as shown in the mouse, rat, and cultured human trabecular meshwork cells and perfused anterior chambers 78,80,93 .…”
Section: Intraocular Pressure (Iop) Controlmentioning
confidence: 99%
“…The ciliary body epithelium can be reached by gene therapy vectors via intravitreal injection (Figures 2 and 3). 94,117 Recently, a team of investigators achieved a reduction of aqueous humor production in experimental mouse models of corticosteroid and microbead‐induced ocular hypertension following an intravitreal AAV administration that resulted in disruption of the aquaporin 1 ( AQP1 ) gene within the ciliary epithelium by use of CRISPR‐Cas9 gene editing 117 …”
Section: Intraocular Pressure (Iop) Controlmentioning
confidence: 99%
See 1 more Smart Citation